2021
DOI: 10.1111/cen.14441
|View full text |Cite
|
Sign up to set email alerts
|

Circulating chemerin level is associated with metabolic, biochemical and haematological parameters—A population‐based study

Abstract: Objective: This study aims to analyse the association of chemerin levels with several metabolic, biochemical and haematological parameters in a large Taiwanese population with relative healthy status.Design: Cross-sectional study.Methods: Data of 4101 healthy participants without history of hypertension, diabetes, dyslipidaemia and renal insufficiency from Taiwan Biobank were analysed. The demographic, biochemical and haematologic parameters were retrieved from the database. Chemerin levels were measured using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Also systolic and diastolic blood pressure were selected to contribute to the variation of chemerin. Similar results were previously reported for an association between chemerin and impaired renal function 39,40 and other metabolic phenotypes that may lead to liver and kidney damage 4,41,42 . Our findings for blood pressure are supported by mechanistic research on chemerin that has been focused on the vascular system and hypertension 43 .…”
Section: Discussionsupporting
confidence: 90%
“…Also systolic and diastolic blood pressure were selected to contribute to the variation of chemerin. Similar results were previously reported for an association between chemerin and impaired renal function 39,40 and other metabolic phenotypes that may lead to liver and kidney damage 4,41,42 . Our findings for blood pressure are supported by mechanistic research on chemerin that has been focused on the vascular system and hypertension 43 .…”
Section: Discussionsupporting
confidence: 90%
“…While concentration of chemerin in plasma of the healthy human subject was approximately 50 ng/mL, that in the obese subjects that were related to hypertension through the augmentation of SNA was increased to 350 ng/mL [26,27]. Furthermore, it was reported that concentration of chemerin in plasma correlated positively with increased systemic blood pressure [28]. Thus, it was expected that chemerin, which was increased in peripheral tissue with hypertension, acted on central nervous system in SHR, and mediated pressor response through the augmentation of SNA.…”
Section: Discussionmentioning
confidence: 99%
“…There are limited comparative data on any potential differences in circulating chemerin levels in men and women; some studies have shown that women have higher chemerin levels than men [ 91 , 92 ], but other studies have reached the opposite conclusion [ 93 ]. Although reports are available on chemerin levels in different racial or ethnic groups, the influence of this factor on circulating chemerin has not been formally compared within a single study to our knowledge.…”
Section: Chemerin Forms and Diseasementioning
confidence: 99%
“…The role of chemerin in pediatric and gestational diabetes will not be discussed here, although there is good evidence of its involvement [ 100 , 101 ]. There are many reports describing chemerin levels along with other adipokines in various cohorts showing that chemerin levels are associated with disorders involved with energy balance [ 81 , 82 , 92 , 102 ]. Those reports are in agreement that levels of circulating chemerin are higher in people with obesity.…”
Section: Chemerin Forms and Diseasementioning
confidence: 99%